Associations between selected allergens, phthalates, nicotine, polycyclic aromatic hydrocarbons, and bedroom ventilation and clinically confirmed asthma, rhinoconjunctivitis, and atopic dermatitis in preschool children. (19th August 2013) - Callesen, M.; Bekö, G.; Weschler, C. J.; Sigsgaard, T.; Jensen, T. K.; Clausen, G.; Toftum, J.; Norberg, L. A.; Høst, A.
Abstract Previous studies, often using data from questionnaires, have reported associations between various characteristics of indoor environments and allergic disease. The aim of this study has been to investigate possible associations between objectively assessed indoor environmental factors and clinically confirmed asthma, rhinoconjunctivitis, and atopic dermatitis. The study is a cross‐sectional case–control study of 500 children aged 3–5 years from Odense, Denmark. The 200 cases had at least two parentally reported allergic diseases, while the 300 controls were randomly selected from 2835 participating families. A single physician conducted clinical examinations of all 500 children. Children from the initially random control group with clinically confirmed allergic disease were subsequently excluded from the control group and admitted in the case group, leaving 242 in the healthy control group. For most children, specific IgE's against various allergens were determined. In parallel, dust samples were collected and air change rates were measured in the children's bedrooms. The dust samples were analyzed for phthalate esters, polycyclic aromatic hydrocarbons (PAH), nicotine, and various allergens. Among children diagnosed with asthma, concentrations of nicotine were higher (P < 0.05) and cat allergens were lower (P < 0.05) compared with the healthy controls; air change rates were lower for those sensitized (specific IgE+) compared with those not sensitized (specific IgE−, P < 0.05); and dust mite allergens were higher for specific IgE+ cases compared with healthy controls (P < 0.05). When disease status was based solely on questionnaire responses (as opposed to physician diagnosis), significant associations were found between di(2‐ethylhexyl) phthalate (DEHP) and dog allergens in dust and current wheeze.